Kajian Terhadap Kitab Mazmur 52:1-10 Dalam Upaya Berteologi Kontekstual Tentang Pohon Zaitun dan Relevansinya Dengan Pohon Pala di Pulau Siau - Tulende, Rullyanty M. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This scientific work discusses the study of olive trees described in general according to the Bible and specifically according to the passage of Psalm 52: 1-10, as an effort to do contextual theology in its relevance to nutmeg trees. Therefore, the paper uses a literature study, as well as understanding the phenomena of what is experienced by the research subjects such as perceptions, motivations, actions and others holistically in the form of words, language, and culture so as to produce a concept of contextual theology based on existing topics to be communicated with the congregation today.